ANTI-INFLAMMATORY EFFECTS OF Graptophyllum pictum (L.) GRIFF EXTRACT IN PRECLINICAL RATS HIND-PAW EDEMA MODELS: A LITERATURE REVIEW - Shofiy, Alifya Rayyani; Makiyyah, Feda Anisah (The SDGS Forum Communication, 2025)
Graptophyllum pictum (L.) Griff or daun ungu is a common medical plant in Indonesia that possesses many promising medical properties, including anti-inflammation. This review aims to discuss the anti-inflammatory effects of Graptophyllum pictum (L.) Griff extract in preclinical hind-paw edema animal models. Through literature search and analyze based on keywords, PICO, inclusion, and exclusion criteria, a total of four studies were included in this review. As a result, ethanol extract of Graptophyllum pictum (L.) Griff shows anti-inflammatory effects significantly reducing the volume of edema and having high anti-inflammatory power by inhibition of the arachidonic inflammatory pathway. Therefore, these preclinical test studies confirmed the anti-inflammatory effects of Graptophyllum pictum (L.) Griff. However, further studies and human trials are required to confirm the efficacy and develop a standardized formula for Graptophyllum pictum (L.) Griff.